Successful Discontinuation of Infliximab in a Refractory Case of Vasculo-Behçet Disease - Akihiro Nakamura; Tomoya Miyamura; Eiichi Suematsu (Case Reports in Rheumatology)
Reports have shown that antitumor necrosis factor alpha (anti-TNF-α) agents including infliximab (IFX) can dramatically suppress the disease activity of refractory vasculo-Behçet disease (vasculo-BD). However, it is completely unknown whether we can discontinue anti-TNF-α agents under clinical remission. A 31-year-old patient with vasculo-BD was initially treated with a high dose of steroid and intravenous cyclophosphamide therapy. Six months later, however, the disease recurred. IFX was administered and immediately the disease activity was reduced. Fortunately, we could discontinue IFX after 18-month remission and no recurrence has been observed. Based on previous reports and our patient, all patients who could discontinue IFX sustained clinical remission for at least one year, continued taking immunosuppressive agents such as methotrexate and azathioprine, and had vascular involvements only in non-life-threatening major vessels such as leg or arm arteries/veins. This is a report suggesting the possibility of discontinuation of IFX in vasculo-BD.